Identification of an additional gene required for eukaryotic nonsense mRNA turnover. - Lee, B S (1995)
Loss of function of any one of three UPF genes prevents the accelerated decay of nonsense mRNAs in Saccharomyces cerevisiae. We report the identification and DNA sequence of UPF3, which is present in one nonessential copy on chromosome VII. Upf3 contains three putative nuclear localization signal sequences, suggesting that it may be located in a different compartment than the cytoplasmic Upf1 protein. Epitope-tagged Upf3 (FLAG-Upf3) does not cofractionate with polyribosomes or 80S ribosomal particles. Double disruptions of UPF1 and UPF3 affect nonsense mRNA decay in a manner indistinguishable from single disruptions. These results suggest that the Upf proteins perform related functions in a common pathway.